Quality of Life and Sexual Function 2 Years After Vaginal Surgery for Prolapse. Issue 6 (June 2016) - Lukacz, Emily S.; Warren, Lauren Klein; Richter, Holly E.; Brubaker, Linda; Barber, Matthew D.; Norton, Peggy; Weidner, Alison C.; Nguyen, John N.; Gantz, Marie G.
Abstract : OBJECTIVE: To longitudinally assess the effect of native tissue vaginal apical prolapse repair with anti-incontinence surgery on quality of life, sexual function, and body image between uterosacral and sacrospinous suspensions. METHODS: A planned secondary analysis was performed on 374 women enrolled in a randomized trial of the two types of native tissue repair for apical prolapse. Condition-specific and generic quality of life, sexual function, overall and de novo dyspareunia, and body image were assessed using validated instruments at baseline; 6, 12, and 24 months postoperatively; and changes from baseline were assessed and compared between surgical groups. General linear mixed models were used for comparisons and clinically significant differences were assessed using minimum important differences. RESULTS: Of the women randomized, 82% had outcomes available at 2 years. Overall, clinically and statistically significant improvements in generic and condition-specific quality of life and sexual function were observed after surgery. Dyspareunia rates decreased from 25% to 16% by 24 months with only 3% of all women undergoing treatment. De novo dyspareunia occurred in 5% and 10% by 12 and 24 months, respectively. Body image scores also significantly improved from baseline. There were no clinically meaningful or statistically significant differences between groups for any of these outcomes (all P >.05). CONCLUSION: Native tissue vaginal prolapse surgery results in statistically and clinically significant improvements in quality of life, sexual function, and body image at 24 months with no significant differences between uterosacral and sacrospinous suspensions. One in 10 women experience de novo dyspareunia but few requested treatment. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, www.clinicaltrials.gov, NCT00597935. Abstract : Supplemental Digital Content is Available in the Text.Uterosacral and sacrospinous transvaginal vault suspensions similarly improve quality of life with low rates of dyspareunia.